Taxonomy of Three Oxytrichids (Protozoa, Ciliophora, Hypotrichia), With Establishment of the New Species Rubrioxytricha guangzhouensis spec. nov. - Luo, Xiaotian; Huang, Jie; Bourland, William A.; El-Serehy, Hamed A.; Al-Farraj, Saleh A.; Chen, Xumiao; Song, Weibo (Frontiers in Marine Science, 2021)
Two oxytrichid ciliates collected from China, Oxytricha lithofera Foissner, 2016 and Rubrioxytricha haematoplasma (Blatterer and Foissner, 1990) Berger, 1999 were investigated based on living observations, protargol preparations, and molecular analyses. The Chinese population of O. lithofera shares highly distinctive features with the type population, e.g., lithosomes, abutting macronuclear nodules, straight undulating membranes, and long dorsal bristles. The morphology and morphogenesis of our new isolate of R. haematoplasma corresponds well with the type population. The 18S rRNA gene sequences of both species were obtained, and the molecular phylogeny of the genera Oxytricha Bory de Saint-Vincent in Lamouroux et al., 1824 and Rubrioxytricha Berger, 1999 was analyzed. In addition, we found that the Guangzhou population of R. haematoplasma described by Chen et al. (2015) can be distinguished from the type population and our isolate by the reddish-brown cortical granules (vs. lemon yellowish to greenish) and mitochondria-like granules present (vs. absent), as well as the slightly red cytoplasm (vs. slightly orange) and the marine or brackish water habitat (vs. freshwater). In addition, a 20-bp divergence in their 18S rRNA gene sequences indicates that they are not conspecific. Thus, we establish a new species, Rubrioxytricha guangzhouensis, for R. haematoplasma sensu Chen et al. (2015).